Synthesis and Tribological Properties of Zeolitic Imidazolate Framework-8 Nanocrystals and Microcrystals - Sun, Wei-Chao; Shi, Qi; Xu, Hong; Dong, Jin-Xiang (Asian Journal of Chemistry, 2014)
The nano- and microcrystalline zeolitic imidazolate framework-8 (ZIF-8) were synthesized using two different methods and had average diameters of approximately 100 nm and 1-10 μm, respectively. The tribological properties of ZIF-8 nano- and microcrystals as additives in a base oil (PEG200) were evaluated using a four-ball tester. Both products exhibited good friction behavior when used as additives in PEG200. In particular, when 0.5 wt. % nanocrystalline or microcrystalline ZIF-8 was added to PEG200, the tribological properties of the oil improved: its maximum nonseizure load (PB) increased by 7.60 and 17.25 % for the nanocrystalline and microcrystalline ZIF-8, respectively; and its wear scar diameters (WSD) decreased by 31.35 and 30.76 %, respectively.